Environmental and technological aspects of redox processes - Vaseashta, Ashok 1954-; Duca, Gheorghe 1952- (IGI Global, 2023)
"Environmental and technological aspects of redox processes is a comprehensive guide to understanding the natural process of electrochemical oxidation/reduction and adsorption action in water treatment technology. The book examines the complexities of redox signaling at a cellular level and how it influences a wide range of biological processes, such as immune function, tissue repair, and cell development. With contributions from leading experts in the field, this book provides valuable insights and strategies for preventing the negative effects caused by oxidants, such as damage to living cells, DNA, proteins, and lipids. Through extensive research on electronic structure, thermodynamics, kinetics, and catalysis of the redox reactions, this book is poised to contribute to an extensive body of new knowledge regarding the essence of the redox processes, the revelation and theoretical justification of key mechanisms, and the discovery of new aspects of methods to control the redox reactions. This will have a major impact on the quality of life, human health, food quality, as well as the state of the environment, especially for the sources of clean water, which continue to deplete at a rapid rate.This book is a valuable resource for professionals and researchers in materials science, materials engineering, chemical engineering, ecological chemistry, and water professionals, as well as individuals working in related disciplines such as environment, chemistry, toxicology, administrative sciences and management, education, sociology, and subjects related to public policies and decision support. Moreover, the book provides insights and support to executives concerned with the management of expertise, knowledge, information, and policy development in different types of science and educational communities."--
Keywords: Oxidation-reduction reaction